Urinary Biomarkers and Overactive Bladder Symptoms Before and After Prolapse Surgery. Issue 2 (February 2023) - Maetzold, Erin C.; Santillan, Donna A.; Kenne, Kimberly A.; Bradley, Catherine S.; Ten Eyck, Patrick; Wendt, Linder; Funk, Meghan; Kowalski, Joseph T.
Abstract : Importance: Women with pelvic organ prolapse (POP) have increased prevalence of overactive bladder (OAB) and the evaluation of urinary biomarkers associated with OAB in the setting of POP is limited. Objective: The objective is to determine whether associations exist between urinary biomarkers measured before POP surgery with postoperative OAB symptoms. Study Design: In this prospective cohort study, women with anterior and/or apical POP beyond the hymen undergoing POP surgery were assessed using the OAB Questionnaire Short Form (OAB-q SF) and the Urogenital Distress Inventory 6 (UDI-6) preoperatively and 3 months postoperatively. A first morning voided urine specimen was collected preoperatively and 3 months postoperatively. Urinary biomarkers for inflammation, neuroinflammation, and tissue remodeling were measured. Univariate generalized linear models measured the relationship between biomarkers and symptoms. Between- and within-cohort assessments were made using 2-sample paired and unpaired t tests, respectively. Results: Seventy-seven participants with OAB (n = 67, 87.0%) and without OAB (n = 10, 13.0%) were enrolled. Seventy-four participants (96%) completed 3-month follow up. The OAB-q SF and UDI-6 scores significantly improved between preoperative and postoperative measures. Preoperative urinary biomarkers did not demonstrate significant correlations with postoperative OAB-q SF or UDI-6 scores. No significant differences were measured in preoperative biomarkers between patients with and without OAB or when comparing preoperative and postoperative biomarkers in patients with OAB. Conclusions: Urinary biomarkers for tissue remodeling, inflammation, and neuroinflammation were not significantly correlated with OAB symptoms in a population of patients with OAB and POP.